Crack Analysis in Vertical Pressure Vessels Case Study : Carbon Capture and Storage Pilot Project Gundih - Adrian - Nim: 13114117 , Alvin
Indonesia has abundant reserves and resources of fossil fuels, but with high CO2 content. Therefore, the Indonesian government is developing CCS (Carbon Capture and Storage) technology to overcome the situation. The CCS technology can be used to reduce carbon dioxide (CO2) emissions resulting from the processing of fossil resources. It consists of three main processes: CO2 capturing process, CO2 transportation, and CO2 storage. In order to run those processes, several kinds of equipment are needed, one of them is the pressure vessel. Failure in the design and operation of pressure vessels may inhibit the CCS process. Considering the vessel importance aspect in the CCS process, further assessment of the failure aspect of the vessel is required, particularly in the assessment of crack. Crack failure assessment that performed in this final project is based on API 579 Fit For Service. This assessment is done by conducting a case study on crack that might occur in terms of dimension and type of cracks. In this assessment of the case studies, the type of crack is surface crack inside or outside surface with a longitudinal direction in the shell component. The case study begins with crack dimensions for depth and the crack length are 0,1 in and 1 in respectively. Based on the analysis, a safe crack dimension range is achieved which is 0,1 in for depth and 1 - 5,5 in for length and also 0,2 in for depth and 1 in for length. To verify the results of this analysis, stress intensity factors is examined with finite element method. From the results of this verification the range of crack dimensions that have been previously obtained can be stated correctly.